2013
DOI: 10.1126/science.1230155
|View full text |Cite
|
Sign up to set email alerts
|

Spin Torque–Generated Magnetic Droplet Solitons

Abstract: Dissipative solitons have been reported in a wide range of nonlinear systems, but the observation of their magnetic analog has been experimentally challenging. Using spin transfer torque underneath a nanocontact on a magnetic thin film with perpendicular magnetic anisotropy (PMA), we have observed the generation of dissipative magnetic droplet solitons and report on their rich dynamical properties. Micromagnetic simulations identify a wide range of automodulation frequencies, including droplet oscillatory moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
280
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(298 citation statements)
references
References 31 publications
16
280
1
1
Order By: Relevance
“…Depending on the geometry and magnetic properties of the free layer, propagating spin waves (SWs) [5][6][7] , solitonic modes [8][9][10][11] , vortex gyration 12,13 , and magnetic dissipative droplets [14][15][16][17] have been observed. STOs can also be used to generate SWs in physically extended thin films, which is of particular interest for future magnonic applications 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the geometry and magnetic properties of the free layer, propagating spin waves (SWs) [5][6][7] , solitonic modes [8][9][10][11] , vortex gyration 12,13 , and magnetic dissipative droplets [14][15][16][17] have been observed. STOs can also be used to generate SWs in physically extended thin films, which is of particular interest for future magnonic applications 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Each nanocontact can sustain several tens of mA current, which gets spin polarized and transfers angular momentum between the two magnetic layers via the so-called spin-transfer torque (STT) effect [35][36][37] . At sufficiently high current densities (B10 8 A cm À 2 ), STT can sustain continuous precession of the local magnetization underneath the nanocontact and also inject high amplitudes of either localized or propagating spin waves (SWs) into the free layer 20,22,23,[38][39][40][41][42][43] .…”
mentioning
confidence: 99%
“…1(b), we plot a measured magnetoresistance curve [17,19,20] at a fixed current of 27 mA ramping the perpendicular applied field from high to low field at a fixed temperature of 150 K. This shows first the creation (at 1 T) and then the annihilation of the droplet state (0.4 T). Figure 1(c) shows a measured droplet stability map in magnetic field and current space [21,23] built from magnetoresistance curves measured at different applied current at a fixed temperature of 150 K. The no droplet state is plotted in gray and corresponds to a lower resistance state, whereas the green area represents the droplet state, a higher resistance state.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Dissipative magnetic droplet solitons (droplets hereafter) are nonlinear confined wave excitations consisting of partially reversed precessing spins that can be created in films with perpendicular magnetic anisotropy (PMA) through the local suppression of the magnetic damping [16]. Droplets have been experimentally created using the STT effect in nanocontacts to PMA films [17][18][19][20][21][22][23], and droplets are a particular case of STToscillators. Recently reported experiments have shown that the stability of these collective excitations is limited by the appearance of drift instabilities, which were attributed to the disorderlocal variations of the effective magnetic field [21,24].…”
Section: Introductionmentioning
confidence: 99%